Highly compact magneto-optical switches for metal-dielectric-metal plasmonic waveguides - Haddadpour, Ali; Nezhad, Vahid Foroughi; Yu, Zongfu; Veronis, Georgios (Optics letters, 2016)
We introduce highly compact resonant-cavity-enhanced magneto-optical switches for metal-dielectric-metal (MDM) plasmonic waveguides. The field profile of the fundamental mode of a MDM waveguide in which the metal is subject to an externally applied static magnetic field is asymmetric. The static magnetic field induced asymmetry, which enhances or reduces the coupling between the waveguide and a side-coupled resonator, and the relatively large induced wave vector modulation are used to design a Fabry-Perot cavity magneto-optical switch, consisting of a MDM waveguide side-coupled to two MDM stub resonators. The on and off states correspond to either the presence or the absence of the externally applied static magnetic field.